KUALITAS PAPAN PARTIKEL DARI PELEPAH KELAPA SAWIT DENGAN PEREKAT DAMAR - Didik Agus Sulaiman1; Farida Hanum Hamzah2; Sonia Somadona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Midrib of palm oil is one of palm oil plantation waste which is abundant and didn’t optimally utilized. This study aims to obtain the best resin adhesive concentration in making of particle board from palm oil midrib. The study was done experimentally using a completely randomized design (CRD) with 5 treatments and 3 replications. The treatments of palm oil midrib and resin adhesive were 90% :10%, 85%: 15%, 80%: 20%, 75%: 25%, and 70% : 30%. The Data obtained were analyzed statistically using Analysis of Varience (ANOVA) and Duncan's New Multiple Range Test (DNMRT) in the level of 5%. The results showed that the composition of palm oil midrib and resin adhesive significantly affected water content, water absorption, thick development, modulus of elasticity, and modulus of rupture but it didn't have significant effect on density. The best treatment in this study was P5 treatment with density of 0,80 g.cm-3, water content of 9,11%, water absorption of 213,12%, thick development of 132,11%, modulus of elasticity of 3.159,48 kgf.cm-2, and modulus of rupture of 19,17 kgf.cm-2. Keywords: Particle board, palm oil midrib, resin adhesive